HUBUNGAN PEMBERIAN SUSU FORMULA DENGAN KEJADIAN DIARE PADA BAYI UMUR 0-6 BULAN DI PUSKESMAS RAWAT INAP PANCUR BATU KECAMATAN PANCUR BATU - Sarika; Apriany Ramadhan Batubara (Jurnal Medicare, 2025)
Diarrhea is a condition in which stools become soft or runny and occur repeatedly (more than 3 times a day). According to the WHO, diarrhea causes the deaths of up to 2 million children worldwide each year, usually due to poor formula feeding practices, such as bottle hygiene, formula preparation methods, and the types of formula given to babies. The design of this study is a descriptive analytical survey with a cross sectional approach, using primary data collected through questionnaires with 30 respondents. Data analysis was carried out using the Chi-Square test. Based on the frequency distribution of the relationship between formula milk provision and the incidence of diarrhea in infants aged 0-6 months at the Pancur Batu inpatient health center, Pancur Batu sub-district, that of the 30 samples, the majority of respondents were included in the Less Good category, as many as 18 people (60%) with 8 people experiencing diarrhea (27%) and 10 people not experiencing diarrhea (33%), the Good category was 9 people (30%) with a total of 9 people not experiencing diarrhea (30%), the Not Good category was 3 people (10%) and all of them experienced diarrhea as many as 3 people (10%). From the results of the Chi-Square test with a confidence level of 90% and df = 2, the calculation results were obtained, namely X2 count 10.861 > X2 table 3.605. This shows that the value of X2 count> X2 table, so H0 is rejected and Ha is accepted. Based on the research results, it was concluded that there was a relationship between giving formula milk and the incidence of diarrhea in infants aged 0-6 months at the Pancur Batu inpatient health center, Pancur Batu sub-district in 2025. It is hoped that health workers will pay more attention to the community, especially mothers who provide formula milk appropriately and correctly.